Self-collected mid-nasal swabs and saliva specimens, compared with nasopharyngeal swabs, for SARS-CoV-2 detection in mild COVID-19 patients. Issue 6 (December 2021) - Alemany, Andrea; Millat-Martinez, Pere; Ouchi, Dan; Corbacho-Monné, Marc; Bordoy, Antoni E.; Esteban, Cristina; Hernández, Águeda; Casañ, Cristina; Gonzalez, Victoria; Costes, Gèlia; Capdevila-Jáuregui, Mar; Torrano-Soler, Pamela; et al.
Highlights: Self-collected nasal and saliva samples can be used for SARS-CoV-2 screening. Self-collected nasal and saliva specimens had a 99% and 90% sensitivity, respectively. Nasopharyngeal swab viral loads correlate better with nasal than saliva. Viral load correlations are poorer at day 7, when lower viral loads are observed.